1996
DOI: 10.1007/bf02942800
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced T-helper 2 lymphocyte responses: Immune mechanism ofHelicobacter pylori infection

Abstract: Several lines of evidence implicate Helicobacter pylori (H. pylori) infection in gastroduodenal inflammation. However, the exact pathogenesis of H. pylori infection is not fully understood. T-helper (TH) lymphocytes may be subdivided into TH1 and TH2 cells based on the distinct patterns of cytokine production. TH1 reaction is associated with immunity or resistance to infection, while TH2 reaction is associated with the progression or persistence of infection. The production of interferon-gamma (INF-gamma) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…While Th1 cytokines (IL-2, IFN-c, TNF-a) are required for host antiviral immune response and are related with tissue injury, Th2 cytokines (IL-4, IL-6 and IL-10) on the other hand typically regulate humoral immune response and their rising levels are often associated with persistent infections [6]. Cytokines released by one type of Th lymphocyte population can downregulate the functions of another Th population [20]. Earlier studies have reported a significant decreased Th1 and increased Th2 cytokines levels in patients with chronic HBV/HCV [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…While Th1 cytokines (IL-2, IFN-c, TNF-a) are required for host antiviral immune response and are related with tissue injury, Th2 cytokines (IL-4, IL-6 and IL-10) on the other hand typically regulate humoral immune response and their rising levels are often associated with persistent infections [6]. Cytokines released by one type of Th lymphocyte population can downregulate the functions of another Th population [20]. Earlier studies have reported a significant decreased Th1 and increased Th2 cytokines levels in patients with chronic HBV/HCV [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies, therefore, are required to determine the role of Lewis antigen mimicry by LPS in the induction of autoimmunity in H. pylori-associated disease. Another and less controversial consequence of Le" expression by H. pylori concerns the down-regulation of the T-lymphocyte response in H. pylori gastritis, T-helper lymphocytes (T,, cells) can be subdivided into T,, and T,, cells, and suppressed T,, and enhanced T,, responses in H. pylori infection may be involved in the immunopathogenesis of this chronic infection [92]. Le" is also found as a surface antigen on the eggs of the parasitic worm Schistosoma mansonii which also down-regulates the T-lymphocyte response during infection [93].…”
Section: Potential Role In Immune Suppression and Autoimmunitymentioning
confidence: 99%
“…Whether IL-2 and IL-4 are secreted is not clear as in one study neither was induced93 whereas both were induced in another 100. Purified urease, Hsp60, and p25 also induce PBMC proliferation,98 102 and Hsp60 stimulates IL-10 but not IFN-γ release by PBMC from infected subjects 102.…”
Section: T Cell Responses To H Pylorimentioning
confidence: 94%